Regulation of human parainfluenza virus type 3 transcription. - Saffran, Holly Anne. (University of Ottawa (Canada), 1995)
To elucidate the roles of the junctional elements in HPIV3 transcription, cDNAs were constructed containing CAT and luciferase reporter genes flanked by sequences representing the HPIV3 termini necessary for transcription, replication and packaging. Mutations to the gene end sequence abolished expression of the upstream and downstream genes. Deleting the gene start sequence at the junction resulted increased expression of the upstream gene, but abrogated downstream gene activity. Alterations in the length of the intergenic trinucleotide resulted in decreased expression of both upstream and downstream genes. Mutations in the sequence of this nontranscribed trinucleotide resulted in decreased activity of the upstream gene but no change in expression of the downstream gene. The gene end sequence does not appear to contain the only signals for termination of transcription. The purine trinucleotide intergenic region is important for termination, but only the presence of three nucleotides appears to be necessary and sufficient for expression of the following gene. Results obtained from assaying reporter activity could often be interpreted in several ways. For example, the data could not distinguish between polymerase readthrough and premature termination. Two RNA detection methods were investigated and show promise as means for detecting and analyzing specific RNA species in transfected cells. (Abstract shortened by UMI.)
Keywords: Biology, Molecular.